Investigation of the Effect of Multimedia Education on Anxiety Before and After Surgery in Patients Undergoing Coronary Artery Bypass Graft Surgery - Kosar Fahimi; Ali Abbasi; Mahdi Zahedi; Farzaneh Amanpour; Maryam Gilani; Hossein Ebrahimi (Hamadan University of Medical Sciences, 2018)
Introduction: Anxiety is one of the prevalent events before and after surgery which occurs in patients due to the waiting time for heart surgery, hospitalization, fear of death, and in general the fear of unknowns. This study was conducted to investigate and compare the effect of multimedia education on anxiety before and after surgery in patients undergoing coronary artery bypass graft surgery. Methods: In this randomized clinical trial where the data collector and the data analyzer were blinded, 110 patients undergoing coronary artery bypass graft surgery in 2016 were divided into two experimental and control groups (each group of 55) using quadruple blocking. For patients in experimental group, training through multimedia method was done and for the control group routine training was done. Patients' anxiety was evaluated using Spilberger's State-Trait Anxiety Inventory 5-7 days before surgery, and the day before surgery and the post-operative after extubation. Data was analyzed using descriptive and analytical statistics (Chi-square, and repeated measures analysis of variance). Results: Both intervention and control groups were homogeneous in terms of demographic variables (P<0.05). There was no significant difference between the mean of State-Trait Anxiety scores between two groups at three times (P<0.05). The mean anxiety score of patients over time was significantly different, so the State, Trait, and total anxiety scores decreased significantly in the time of extubation compared to the previous two stages (P<0.05). Conclusion: Since, by using educational interventions the anxiety of patients was reduced compared to the preoperative situation, preoperative educational interventions are recommended to reduce the anxiety of these patients.